Soil-site suitability evaluation for mustard in calcareous soils of Girnar toposequence in Southern Saurashtra region of Gujarat - Gopal Gandhi; S G Savalia (Journal of Oilseed Brassica, 2026)
The five representative pedons were evaluated for their suitability to Indian mustard [Brassica juncea (L.)Czern & Coss.] in the soils of different land slope of Girnar toposequence of Southern Saurashtra region ofGujarat. The soils of pedon P3 belong to Typic Haplustert are highly suitable for Indian mustard cultivation,whereas the soils of pedon P1 belong to Lithic Ustorthents, pedon P2 belong to Lithic Haplustepts, pedon P4belong to Typic Haplustepts and pedon P5 belong to Typic Ustifluvents are currently not suitable for Indianmustard cultivation. Topography, shallow soil depth, high CaCO3, drainage, salinity and sodicity are the majorlimitations in most soils of Girnar toposequence of Southern Saurashtra. Results showed that the suitabilityclasses can be improved if the correctable limitations (soil fertility characteristics) are altered through soilamelioration measures.